Age-related changes in peripheral blood counts in humans - Mahlknecht, Ulrich Rudolph; Kaiser, Simone (Experimental and Therapeutic Medicine, 2010)
Anaemia has become a common concern in geriatric health. Since its prevalence varies quite significantly among different groups depending on factors such as ethnicity, lifestyle or fitness, the appropriateness of the current WHO definition of anaemia in the elderly may be questioned. We evaluated peripheral blood parameters from 1,724 individuals (908 women aged 18-101 years and 816 men aged 18-96 years), who were treated at the University of Heidelberg Medical Center with no known haematological history.
Gesehen am 02.05.2023